Partial Purification and Kinetic Study of Xanthine Oxidase from Serum of Hyperuricemia Patients - Rana F. Jameel; Layla A. Mustafa (African Journal of Advanced Pure and Applied Sciences, 2022)
The research included Xanthine oxidase isolation and purification from serum of patients with hyperuricemia and estimation its approximate molecular weight by using two techniques; gel filtration chromatography by using Sephadex G-200 and by electrophoresis by using SDS. Sixteen ml of serum as collected for isolation from patients with hyperuricemia from Al- Salam Hospital in Mosul, Iraq, for period from September to December 2021, their ages ranged from (25 years and above). The results showed that there are a significant increase in the activity of XO in serum of patients with hyperuricemia (29.23 ± 2.21) U/L compared to control group (8.38 ± 0.92) U/L at the probability level (p≤ 0.05). XO was isolated by different biotechnologies. One proteinous band was isolated from ammonium sulfate solution using gel filtration chromatography with specific activity (5.2) U/L, and the recovery percentage was (89.8%), and the number of purification times was equal to (7.1). The molecular weight was estimated using gel filtration and it was in the limits of 218776 Daltons approximately, While by using SDS-PAGE it was equal to 221513 Daltons approximately. Also the study determined to find the optimal conditions for the activity of XO, Where the maximum activity was obtained by using (150 µL) of the partially purified enzyme and pH (8.2), at temperature (40 ºC) with a rection time 5 minute and at concentration of (0.35 mM) of the substrate (xanthine). The maximum velocity (Vmax) and Michaelis-Menten constant (km) value were determined using Linweaver- Burk plot and it was equal to was (41.6) U/L and (0.0952) mM, respectively.